2015
DOI: 10.1016/j.jmau.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Can vitamin C affect the KBrO3 induced oxidative stress on left ventricular myocardium of adult male albino rats? A histological and immunohistochemical study

Abstract: Potassium bromate (KBrO3) cardiotoxicity is not widely recognized, in spite of its well known oxidative cell and tissue damage. The wide exposure to KBrO3 in food and water necessitates finding of a simple and available antidote for its hazards like vitamin C. There are growing evidences that the regulation of redox reactions in cells is intimately tied to the levels of antioxidants. As the heart is highly vulnerable for oxidative damage, left ventricle muscle was the spotlight of our study. For this purpose 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Additionally, it was demonstrated that free radicals and/or oxidative stress were mediated by the effect of KBrO3, which is fully consistent with previous reports that KBrO3 induces damage via oxidative stress (10)(11)(12). Cardiac injury induced by KBrO3 has also been observed in rats (15,16), and histological evidence demonstrates that KBrO3 induces cardiac apoptosis and/or necrosis in rodents (33). However, cardiac hypertrophy induced by KBrO3 has not been previously examined.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, it was demonstrated that free radicals and/or oxidative stress were mediated by the effect of KBrO3, which is fully consistent with previous reports that KBrO3 induces damage via oxidative stress (10)(11)(12). Cardiac injury induced by KBrO3 has also been observed in rats (15,16), and histological evidence demonstrates that KBrO3 induces cardiac apoptosis and/or necrosis in rodents (33). However, cardiac hypertrophy induced by KBrO3 has not been previously examined.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, KBrO3 at a dose of 20-30 mg/kg damages cardiac tissues in rats (16). The histological evidence also demonstrates that KBrO3 at 20 mg/kg twice weekly for 4 weeks induces cardiac fibrosis in rats (33). In a clinic, nine cases of accidental KBrO3 poisoning in a bakery demonstrated hematemesis and renal failure as the possible adverse outcomes (48).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts represents one of the main myocardial cell populations which increased in number due to cardiac diseases and toxicity. The increased fibroblast number can be due to different mechanisms such as endothelial and epithelial cells transformation into myofibroblast and fibroblasts; increased myocardial fibroblasts replications and circulating bone marrow cells migration and transformation into fibroblast [37,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity studies with experimental rats have shown that potassium bromate exerts; cardiac toxicity [ 18 ]; toxicity of the bone and blood [ 19 ]; liver/hepatic tissue and renal toxicity [ 20 ] etc. Several studies have also demonstrated its carcinogenicity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%